1990
DOI: 10.1017/s0016672300035370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate on X-Ray and bleomycin-induced chromosome aberrations in human peripheral blood lymphocytes

Abstract: Peripheral blood lymphocytes from normal human volunteers or from Down syndrome patients were pre-treated with sodium butyrate (a compound which is known to induce structural modifications in the chromatin through hyperacetylation of nucleosomal core histones) and exposed to X-irradiation or treated with bleomycin in vitro in the G0 and/or G1 stage(s) of the cell cycle. The frequencies of chromosomal aberrations in the first mitosis after treatment were scored. The results show an enhancement in the yield of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Nevertheless, butyrate may also act as co-mutagen, since we present evidence that the induction of cell dierentiation by butyrate attenuates p53-dependent DNA damage response. Co-mutagenic features (Sankaranarayanan et al, 1984;Hojo et al, 1994), even a direct mutagenic eect of butyrate (Utesch et al, 1993), are reported by others. Both, anti-neoplastic and co-carcinogenic in vitro eects of butyrate may be correlated to in vivo observations, as epidemiological studies suggest an important role of butyrate in the prevention of colorectal cancer (Stemmermann and Yatani, 1972;Howe et al, 1992).…”
Section: Concentration Of Butyratementioning
confidence: 73%
“…Nevertheless, butyrate may also act as co-mutagen, since we present evidence that the induction of cell dierentiation by butyrate attenuates p53-dependent DNA damage response. Co-mutagenic features (Sankaranarayanan et al, 1984;Hojo et al, 1994), even a direct mutagenic eect of butyrate (Utesch et al, 1993), are reported by others. Both, anti-neoplastic and co-carcinogenic in vitro eects of butyrate may be correlated to in vivo observations, as epidemiological studies suggest an important role of butyrate in the prevention of colorectal cancer (Stemmermann and Yatani, 1972;Howe et al, 1992).…”
Section: Concentration Of Butyratementioning
confidence: 73%
“…Although not demonstrated with GHB, butyric acid itself has been shown to cause an increase in histone acetylation, leading to an enhancement of transcriptional rates and alteration in the expression of genes. 16 Treatment of cells with this chemical has also been shown to increase the frequency of Alu1-, X-ray-, and bleomycin-induced chromosomal aberrations, 17 and in other cases to enhance the subsequent mutagenic response of cells to mutagenic agents. 18 Similarly, there is little data available on the genotoxicity (or lack of it) of GBL, although a related chemical, 4-(N-butylnitrosoamino)-4-hydroxybutyric acid lactone, was highly mutagenic in a number of bacterial tests.…”
Section: Discussionmentioning
confidence: 99%
“…Although not demonstrated with GHB, butyric acid itself has been shown to cause an increase in histone acetylation, leading to an enhancement of transcriptional rates and alteration in the expression of genes 16. Treatment of cells with this chemical has also been shown to increase the frequency of Alu1 ‐, X‐ray‐, and bleomycin‐induced chromosomal aberrations,17 and in other cases to enhance the subsequent mutagenic response of cells to mutagenic agents 18…”
Section: Discussionmentioning
confidence: 99%